Nurse-Led Gastrostomy Care: A Business Case - Davide Fernandes; Ana Lopes (Onco.News)
Percutaneous gastrostomy tube placement is a crucial method for providing long-term enteric nutrition in patients with cancer. The process involves four stages: decision-making consultation, hospital admission, device implantation in a hybrid operating room, and discharge to the community. Post-discharge care is typically physician-led, aligning with Portuguese health policies. However, expanding nurse-led interventions could alleviate physician burden, enhance care integration, and improve outcomes such as quality of life, patient engagement, and satisfaction. Nurses’ involvement, guided by clinical expertise and person-centered care principles, ensures effective follow-up tailored to individual needs. While nurse-led care shows promise, its economic impact remains underexplored, raising concerns about cost-efficiency in community-based gastrostomy management. This article advocates for a nurse-led model to optimize care for gastrostomy patients, addressing gaps in current practices while maintaining quality and potentially achieving greater cost-effectiveness.